PELABUHAN PANJANG SEBAGAI MAIN PORT DIKAWASAN SUMATERA BAGIAN SELATAN - Devi Arnita (SOSIALITA, 2018)
Port of Panjang in Bandar Lampung is the main port commercial of Lampung Province which becomes the gate economic connectivity Lampung province that serves as the backbone of development in Lampung and South Sumatra region in general. So expect the Port of Panjang could be the main port to conduct a comparative study with the Port of Tanjung Priok. However, various constraints exist to make the Port of Panjang as the main port. The constraints include lack behind in terms of infrastructure and superstructure also the performance port of operations is still far when compared with the Port of Tanjung Priok. Port of Panjang in this case less attractive by main line operators (major carriers) from the carrier vessels that are large (mother vessel) for unloading and transhipment activities. The method used in this study is a qualitative and quantitative comparability between the Port of Panjang with the Port of Tanjung Priok in each container terminal. This research data collection was done by direct observation in the study site to obtain the required data. Besides the data collection is done through primary and secondary data collection. Primary data were collected by means of surveys, with the aim of examining the location directly. The survey was conducted by interview or questionnaire.